Societal perspectives on community pharmacy services in West Bank - Palestine - Khdour MR; Hallak HO (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
Understanding the public's view of professional competency is extremely important; however little has been reported on the public's perception of community pharmacists in PalestineObjectives: To determine the perception of Palestinian consumers of the community pharmacist and the services they offerMethod: This project used the survey methodology administered by structured interviews to consumers who attended the 39 randomly selected pharmacies, in six main cities in Palestine. The questionnaire had range of structured questions covering: Consumers' patronage patterns, consumers' interaction with community pharmacists, consumers' views on how the pharmacist dealt with personal health issues, procedure with regard to handling private consultations.Results: Of 1,017 consumers approached, 790 consumers completed the questionnaire (77.7 %). Proximity to home and presence of knowledgeable pharmacist were the main reasons for patients to visit the same pharmacy. Physicians were identified as the preferred source of advice by 57.2% and pharmacists by 23.8%. Only 17% of respondents considered pharmacists as health professionals who know a lot about drugs and are concerned about and committed to caring for the public. In addition, 49% indicated that pharmacists spoke more quietly cross the counter during counseling and almost one third reported that the pharmacist used a private area within the pharmacy. The majority of respondents would be happy to receive different extended services in the community pharmacy like blood pressure monitoring.Conclusions: Palestinian consumers have a positive overall perception of community pharmacists and the services they offer. Awareness should be created amongst the public about the role of pharmacist and the added value they can provide as health care professional. There is a need to consider privacy when giving patient counseling to increase user satisfaction.